2014
DOI: 10.5466/ijoms.12.235
|View full text |Cite
|
Sign up to set email alerts
|

Multi-observer Assessment of Trainee Dentists

Abstract: Multi-observer assessment involves the assessment of a personʼs work behavior by more than one colleague at the same time for the purpose of human resource development and capacity building. In the medical field, multi-observer assessment is employed to provide formative feedback during regular one-on-one meetings in order to increase the professional competence of medical residents, but it is rarely used in dental medicine. This report describes multi-observer assessment of the performance of trainee dentists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…This is based on the global standards proposed by the World Federation for Medical Education (1,2). Cross-sectional studies for each period have been reported regarding education at the pre-graduate clinical practical training and post-graduate clinical training levels (3)(4)(5)(6)(7)(8)(9). However, no studies on a clinical competency examination as an overall evaluation at the end of pregraduate clinical practical training and at the end of OSCAT as a pilot study with the objective of establishing a clinical competency evaluation for professionalism in dental education.…”
Section: Introductionmentioning
confidence: 99%
“…This is based on the global standards proposed by the World Federation for Medical Education (1,2). Cross-sectional studies for each period have been reported regarding education at the pre-graduate clinical practical training and post-graduate clinical training levels (3)(4)(5)(6)(7)(8)(9). However, no studies on a clinical competency examination as an overall evaluation at the end of pregraduate clinical practical training and at the end of OSCAT as a pilot study with the objective of establishing a clinical competency evaluation for professionalism in dental education.…”
Section: Introductionmentioning
confidence: 99%
“…However, evaluation methods vary widely; for example, one learner assessment tool, work-based assessment(WBA), is the method primarily used at medical sites (3)(4)(5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%